Increase in severity of molar-incisor hypomineralization and its relationship with the colour of enamel opacity: a prospective cohort study - Da Costa-Silva, Cristiane M.; Ambrosano, Glaucia M. B.; Jeremias, Fabiano [UNESP]; De Souza, Juliana F. [UNESP]; Mialhe, Fabio L. (Wiley-Blackwell, 2011)
Background. Predicting risk of posteruptive enamel breakdown (PEB) of molar-incisor hypomineralization (MIH) opacity is a difficult but important clinical task. Therefore, there is a need to evaluate these aspects through longitudinal studies.Objective. The aim of this longitudinal study was to analyse the relationship between colours of MIH opacity of children aged 6-12 (baseline) and other clinical and demographic variables involved in the increase in severity of MIH.Materials and methods. A blinded prospective 18-month follow-up was conducted with 147 individuals presenting mild MIH. Tooth-based incidence of increase in severity of MIH (PEB or atypical restorations) was used as dependent measurement. Enamel opacities were recorded according to colour shades of white, yellow and brown, allowing assessment of susceptibility to structural loss over time, according to colour of MIH opacity. Poisson regression models were used to adjust the results for demographic and clinical variables.Results. Brown and yellow MIH opacities were at higher risk for PEB and atypical restorations than those of white ones, even after adjustment for clinical and demographic variables.Conclusion. Teeth presenting mild MIH severity associated with yellow and brown enamel opacities were at high risk for increase in severity of MIH than lighter ones. This result could help clinicians determine a risk-based treatment for children with MIH.